Quality management for footwear used in outdoor activities (Economics and region, 2023)
The condition system "Human physical activity – footwear for active recreation" was studied from the point of view of positive influence on human health. The relevance of scientific research on footwear for active recreation as an obligatory and important component of the material segment of the complex of cultivation, formation and practical implementation of a healthy lifestyle of the population and ensuring its physical health is substantiated. The nomenclature of the main factors ensuring the quality of footwear for active recreation (friction properties (slip resistance), shock absorption (damping (spring) function), flexibility, level of hygiene, harmlessness and bactericide) was established and the main general consumer requirements for the specified properties were outlined. The expediency and advantages of using the method of comprehensive evaluation of the level of quality to determine the degree of suitability of the studied footwear for active recreation to meet the requirements of modern consumers have been proved. Using the complex evaluation algorithm and the results of the study of indicators of individual consumer properties of the studied footwear for active recreation, a comprehensive indicator of its quality was calculated. The results of the research justified the need to develop new materials for active leisure footwear.
Keywords: footwear for active recreation; consumer properties; quality assessment; product characteristics; consumer requirements